The Colombian Strategic Freight Transport Model Based on Product Analysis - Cantillo, Victor; Jaller, Miguel; Holguín-Veras, Jose (Promet - Traffic&Transportation, 2014)
Freight transport modelling at interregional scale is relevant for planning issues. However, freight modelling processes are complex because it is not easy to define the relevant variables in the analysis, and to obtain the required information on freight movements through the network. These facts raise the need to adapt the modelling framework to each context. This paper proposes a strategic national freight transport modelling framework developed as a variant of the traditional four-step modelling process with additional steps to estimate traffic flows from freight flows and to consider empty trips. The country of Colombia is used as the case study to implement and calibrate the proposed model. The data, data sources, and modelling methodologies used for each step are explained. In addition, data limitations and measures taken to complement the available data are discussed. From the implementation, the authors identify a set of advantages derived from the modelling approaches considered and suggestions for improvement.